Smashed tabernacle: Catholic emptiness and nationalism in post-industrial Scotland - Martin, D (Wiley, 2022)
This article considers the ruined megalith of St Peter's, Cardross, an abandoned Catholic seminary. Widely regarded as an architectural masterpiece, it was erected in the mid-1960s when the minority Catholic community of Scotland was staunch and optimistic. Its decline and eventual dereliction reflect the crisis of faith experienced by its congregation and the besmirching of the ideal of the Catholic priesthood by sexual scandal. The idealism and optimism that informed Scottish Catholic subjecthood in the past have recently seen their allegiance transferred to political nationalism. This article deploys the classic anthropological theory of ritual and some recent political and philosophical writing to distil insights into emptiness as a phenomenon of modernity.